Awareness and Use of Academic Social Networking Websites by the Faculty of CIIT - Sheikh, Arslan (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
The popularity and massive usage of online social networking sites is evident to all. There are a number of online social networks that are being widely used by the academic and non-academic community for entertainment. A new branch of these online social networks has emerged which is known as academic social networking websites (ASNWs). The purpose of ASNWs is entirely different from entertainment, as they specifically target scholars. ASNWs are virtual platforms where researchers can create a research profile and communicate with other members. This study aims to explore the awareness, usage and feelings of CIIT faculty members about the five most famous ASNWs namely; ResearchGate, Acedemia.edu, LinkedIn, Mendeley and Zotero. A structured questionnaire was designed and sent to all faculty members of CIIT via email to get the feedback. Findings show that the majority of faculty members are well aware of these ASNWs for the last three years or so. Most of the respondents are members to more than one academic social network. Faculty members also revealed that they visit ASNWs twice in a week for half an hour. The respondents expressed that they mostly use these platforms for following purposes: interacting with experts, promotion/sharing of their research output, participation in discussions, to get ideas about the latest research trends and to get help in resolving research problems. The feelings of CIIT faculty members about using ASNWs were also found very positive. The highest level of usage was reported for LinkedIn followed by ResearchGate, Acedemia.edu, Mendeley and Zotero, respectively.